Importance of zein composition in quality protein maize (QPM) to microstructural and chemical modifications of proteins during extrusion and their impact on texture of corn-based extrudates - Dias Paes, Maria Cristina, author; Stone, Martha B., advisor; Hamaker, Bruce, advisor; Yu, Lucy Liangly, committee member; Chandler, John, committee member (Colorado State University. Libraries, 2002)
Although several studies have been already carried out to clarify the importance of endosperm corn proteins in corn grain hardness and vitreousness, the role that protein compositional differences plays on the physical properties of texturized corn-based products is still poorly understood. Considering that protein has been shown to have an important impact in extruded food systems, it is important to understand how differences in composition or spatial arrangement of corn endosperm proteins, such as observed in Quality Protein Maize (QPM), can influence changes in polymers and structures during extrusion processing. Therefore, the overall objective of this project was to investigate the effect of the high γ-zein content in QPM to chemical, physical, and microstructural changes that occurs in zeins during extrusion and its impact on texture of intermediate corn-based extrudates. Three experiments were designed to test the overall scientific hypothesis that high γ-zein content in QPM influences chemical modifications of proteins during extrusion and provides different textural properties in corn-based extrudates as compared to normal corn. Overall results of thermal and pasting properties for starch isolated from QPM and normal maize grits showed either no or negligible differences between starch of normal and QPM maize types. This finding allowed maize grits to be used in prospective studies for comparison of possible modifications in proteins during processing. Extrusion caused significant changes in the microstructural organization of major components of the grits and the chemistry of maize proteins. Starch granules lost their orderly structure, gelatinized, and melted to form a continuous matrix, whereas, proteins aggregated into large masses diffused in the gelatinized starchy network. The high γ-zein content in QPM seems to confer resistance to disruption of protein bodies during extrusion. Therefore, high γ-zein rich protein bodies require higher energy input within the extruder for complete disruption than protein bodies found in normal maize. But differences in dispersion of zeins in the system for the two maize types were not identified at high shear conditions evaluated in this study. In general, modifications in protein chemistry were driven by both noncovalent and covalent interactions, although disulfide bonding was apparently more important for the QPM samples. Chemical changes in proteins were identified as an important factor influencing brittleness of the final extrudates. Moisture negatively affected the brittleness of extrudates, regardless of maize type. Higher content of γ-zein in QPM likely provided higher strength to maize extrudates thus favoring crispness of extruded maize grits. The use of QPM grits to replace normal grits in the production of extruded corn-based products may promote extended bowl-life of extruded corn flakes as well as enhance crispness of fully expanded snacks.
Keywords: agricultural engineering